Descriptive Study of Septicemia among Children Under Five Years in Wasit Province, Iraq in 2019 (Medico Legal Update, 2021)
Sepsis is a common illness; however, it strikes aged people and very young people in more tendency. Themost susceptible age group of sepsis is children, and more specifically newborns and young infants. Inaddition, underlying health problems increase the risk of illness. The aim of this study is to determineprevalence of septicemia in children under five years in Al-Kut hospital for Gynecology obstetrics andpediatrics, numbers of cases are 135 patients. A descriptive analysis study design was used for the purpose isconducted at Al-Kut hospital for Gynecology obstetrics and pediatrics. There was significant differences inthe prevalence of septicemia among children with different ages. The prevalence of septicemia was higher inthe 1st month of age .Generally, prevalence of septicemia did not significantly affected by gender, howeverage is the most influencer since the infection was higher in children samples which were collected fromstool isolates. At end, to reduce the complication and mortality of septicemia and to prevent sepsis formationinfection including antibiotic-resistant pathogens related infection, research recommend a rapid diagnosisand effective treatment.